2021
DOI: 10.21608/fumj.2021.184699
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D And Serum Ferritin Levels In Male Pattern Hair Loss :Is There A role?

Abstract: Male androgenetic alopecia is the most common cause of alopecia in men. The pathogenesis involves androgen-induced minaturisation of terminal hairs into vellus hairs in affected regions of the scalp. Some degree of follicular minaturisation and consequential hair loss is universal and is considered to be a physiological secondary sexual characteristic. Various studies evaluated serum ferritin level and serum vitamin d levels in patients with alopecia. Most studies done on female patients with alopecia with ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…These findings are consistent with the outcomes of a study led by Tahlawy et al where they noted a mean vitamin D level of 37.1 ng/ml in cases, contrasting with a mean of 44.2 ng/ml in controls. 22 The study revealed significantly lower Vitamin D levels in cases compared to controls, with a p=0.02. Similar results were also reported by Hagag et al, Moneib et al, Rasheed et al, and Banihashemi et al their findings indicated significantly lower levels of vitamin D in cases compared to matched controls.…”
Section: Discussionmentioning
confidence: 77%
“…These findings are consistent with the outcomes of a study led by Tahlawy et al where they noted a mean vitamin D level of 37.1 ng/ml in cases, contrasting with a mean of 44.2 ng/ml in controls. 22 The study revealed significantly lower Vitamin D levels in cases compared to controls, with a p=0.02. Similar results were also reported by Hagag et al, Moneib et al, Rasheed et al, and Banihashemi et al their findings indicated significantly lower levels of vitamin D in cases compared to matched controls.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, Moneib et al 11 reported significantly lower serum 25(OH) D levels in patients with female androgenetic alopecia than in controls, and Samar et al 12 reported significantly lower vitamin D levels in male androgenetic alopecia cases.…”
Section: Discussionmentioning
confidence: 92%
“…Because the literature has widely highlighted the importance of ferritin levels in regards to hair loss, a few studies have been performed to determine if low ferritin levels are also significant in males experiencing hair loss. In the study described previously by Tahlawy et al, the researchers also assessed 30 males with androgenetic alopecia and compared their serum ferritin levels with 30 healthy males [66]. The results showed no statistically significant differences in ferritin levels in patients with androgenetic alopecia compared to controls.…”
Section: Men Vs Womenmentioning
confidence: 94%
“…A case-control study performed in 2021 investigated the role of vitamin D serum levels in 30 males with androgenetic alopecia [66]. Results showed significantly lower vitamin D levels in males with androgenetic alopecia compared to healthy controls (p < 0.01).…”
Section: Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation